Maintaining and repairing old and historic buildings - Cullinane, John J. (Hoboken, New Jersey : John Wiley & Son, Inc., 2013)
A practical guide to the maintenance and repair of old and historic buildings Carrying out work in accordance with the U.S. Secretary of the Interior's standards and guidelines can be a challenge for professionals charged with the preservation, restoration, and care of historic properties. This book-with-CD package facilitates the process with more than 400 field guidelines for the treatment of historic building structures, systems, and materials. It includes: Background and rationale for treatment Annotated standards and guidelines Step-by-step treatment instructions Information on energy conservation and meeting LEED and ADA requirements The treatment guidelines cover a wide range of issues, from how to replace broken glass in wood and metal windows to preparing historic mortar. Each guideline can be printed out individually from the accompanying CD for easy reference and on-site use. Well organized and easy to use, Maintaining and Repairing Old and Historic Buildings is a valuable resource for architects, engineers, facility managers, and related professionals working in the areas of building preservation and restoration - Book Cover
Introduction -- 1. The approach to historic buildings, building systems, and historic materials -- 2. What you need to know -- 3. The standards, guidelines, and other guidance material -- 4. Meeting treatment goals while conserving energy -- 5. Making old and historic buildings accessible -- Index.
Keywords: ARCHITECTURE -- CONSERVATION AND RESTORATION